Zagrożenia i szanse dla pracowników i menedżerów w procesach przejęć i fuzji przedsiębiorstw - wyniki badań - Zając, Czesław (Threats and opportunities for employees and managers in the process of merging and acquisitions of enterprises - research results, 2006)
The empirical research and study of publications made by the author of this paper show, that mergers and acquisitions can generate both threats and opportunities for managers and employees. The strongest feelings of threats are: the loss of the job, the decreasing of salary, the restriction of the corporate authority and authonomy and the development of professional skills. The most expected benefits (opportunities) are: more possibilities of career making, higher salary, better conditions of the work place and the development of professional skills. The sources and the intensity of these threats and opportunities lay in the character of acquisition (friendly or hostile) and in motives of mergers and acquisitions. The results of this empirical research indicate also that managers and employees “evaluate” mergers and acquisitions on the basis of threats more often than on the basis of opportunities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 294-302